Treatment options for severe cardiac amyloidosis: heart transplantation combined with chemotherapy and stem cell transplantation for patients with AL-amyloidosis and heart and liver transplantation for patients with ATTR-amyloidosis - Sack, Falk-Udo; Kristen, Arnt; Goldschmidt, Hartmut; Schnabel, Philipp Albert; Dengler, Thomas; Koch, Achim; Karck, Matthias (European journal of cardio-thoracic surgery, 2008)
Objective: Cardiac amyloidosis (CA) is associated with a poor prognosis and a survival rate of less than 30% 2 years after clinical manifestation. Considered as a semi-malignant disease, CA is often a contraindication for HTx; however, depending on the type of CA, there are excellent treatment regimes that can be combined with HTx. In AL-amyloidosis, chemotherapy and stem cell transplantation are necessary and in TTR-amyloidosis, where the liver is the source of the pathologic protein, liver transplantation is recommended after HTx. Methods and Results: More than 60 patients with AL-amyloidosis and more than 25 patients with ATTR-amyloidosis have been investigated at our centre. Eighteen patients showed signs of end-stage heart failure. Four patients died within 1 month after listing for HTx. Seven patients with AL (mean age 41.8 years) and five patients with ATTR-amyloidosis (mean age 42.6 years) were successfully transplanted with an actual survival rate of 91.6%. One patient died 8 months after HTx due to infection. Five AL patients received chemotherapy and SCT and one ATTR patient was liver transplanted. Three AL patients showed complete remission of amyloidosis. Conclusions: Cardiac amyloidosis is a potentially curative disease after HTx when combined with either chemotherapy and SCT or LiverTx depending on the type of the amyloidosis. Due to the natural course of the disease, urgent HTx after cardiac manifestation is mandatory. With this approach, excellent survival rates and even remission of the underlying disease is possible.
Available online 21 December 2007
Gesehen am 21.01.2022